Glacial dynamics and deglaciation history of Hambergbukta reconstructed from submarine landforms and sediment cores, SE Spitsbergen, Svalbard. (20th November 2020) - Noormets, Riko; Flink, Anne; Kirchner, Nina
Abstract : The submarine landforms and shallow sediment record are presented from Hambergbukta, southeastern Spitsbergen using swath‐bathymetric, subbottom acoustic, and sediment core data. The mapped landforms include large terminal and end‐moraines with associated debrisflow aprons on their distal flanks, drumlinized till surface, glacial lineations, medial and retreat moraines, crevasse squeeze ridge networks, eskers, as well as iceberg‐produced terraces and plough‐marks. Analysis of the landforms and landform assemblages in combination with the sediment core data and aerial imagery studies reveal a complex and dynamic glacial history of Hambergbukta. We present a detailed history of Hambergbreen glacier indicating two previously unknown surges as well as new details on the nature of the subsequent ice‐margin retreat. The results from two gravity cores combined with the shallow acoustic stratigraphy and high‐resolution bathymetry suggest that the c . AD 1900 surge was less extensive than previously thought and the retreat was most likely rapid after the c . AD 1900 and 1957 surges of the Hambergbreen. Mixed benthic foraminifera collected from the outer fjord basin date to 2456 cal. a BP, suggesting older sediments were re‐worked by the c . AD 1900 surge. This highlights the importance of exercising caution when using foraminifers for dating surge events in fjord basins enclosed by prominent end‐moraines.